2017
DOI: 10.5114/pg.2017.68116
|View full text |Cite
|
Sign up to set email alerts
|

Immature granulocytes predict severe acute pancreatitis independently of systemic inflammatory response syndrome

Abstract: IntroductionEarly prediction of severity of acute pancreatitis (AP) by a simple parameter that positively correlates with the activation stage of the immune system would be very helpful because it could influence the management and improve the outcome. Tumor necrosis factor α (TNF-α) and interleukin-1 (IL-1) play a critical role in the pathogenesis systemic inflammatory response syndrome (SIRS) and severity of AP. One of the effects of IL-1 and TNF-α is an increase in the number of immature granulocytes (IGs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…[14][15][16] Recent studies have demonstrated that IG can be used as an effective inflammatory marker. [15,17,18,[25][26][27] Studies on the use of IG measurements in AA diagnosis and the discrimination between SA and CA are limited. [22,28,29] Mathews et al [28] found that an increased IG% was significant in the discrimination of acute and perforated appendicitis in the pediatric age group, but it did not bring any additional benefit to this discrimination when compared with an increased CRP level and shift to left.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Recent studies have demonstrated that IG can be used as an effective inflammatory marker. [15,17,18,[25][26][27] Studies on the use of IG measurements in AA diagnosis and the discrimination between SA and CA are limited. [22,28,29] Mathews et al [28] found that an increased IG% was significant in the discrimination of acute and perforated appendicitis in the pediatric age group, but it did not bring any additional benefit to this discrimination when compared with an increased CRP level and shift to left.…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ age, gender, etiology of AP, laboratory parameters, Ranson score, revised Atlanta classification, duration of hospital stay and mortality rates were recorded. The revised Atlanta classification (mild: no organ failure and no local or systemic complications; moderately severe: transient organ failure (< 48 h) and/or local or systemic complications without persistent organ failure (> 48 h); severe: persistent organ failure (> 48 h): single organ failure or multiple organ failures) was used to diagnose the severity of AP [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the elderly population increasing, it is important to determine the prognosis of AP in the geriatric population. There are many scoring systems and laboratory parameters to determine the prognosis [ 3 6 ]. Ranson Criteria, Modified Glasgow Score, Acute Physiology and Chronic Health Evaluation II (APACHE II) are widely used scores.…”
Section: Introductionmentioning
confidence: 99%
“…Acute pancreatitis is a relatively common disease and severe acute pancreatitis (SAP) is associated with a high mortality rate, ranging from 15–40% ( 1 ). SAP starts as a local inflammation of pancreatic tissue and is characterized by the development of systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction ( 2 , 3 ). Unfortunately, despite several years of experimental and clinical research, the precise pathophysiology of SAP, particularly in the clinical context remains unclear.…”
Section: Introductionmentioning
confidence: 99%